ANALISIS BURNOUT DAN WORK LIFE BALANCE TERHADAP TURNOVER INTENTION DI MASA PANDEMI COVID-19 - Exacta, Egivzi Arya; Komariah, Kokom; Saori, Sopyan (Procuratio : Jurnal Ilmiah Manajemen, 2022)
The purpose of this study is to determine the effect of burnout and work life balance on turnover intention. The methods used in this research are descriptive and associative in a quantitative way. The sampling technique used in this study was the saturated sampling technique. The samples selected in this study were 63 employees of Sparks Forest Adventure. The data analysis techniques used in this study are multiple correlation analysis techniques, coefficient of determination analysis, multiple linear regression analysis,partial significant test and simultaneous significant test. Based on the results of the multiple correlation coefficient test, an R value of 0.743 means that there is a strong relationship between burnout and work life balance on turnover intention at Sparks Forest Adventure. The results of the coefficient of determination test were obtained from the acquisition of a value of 0.553, meaning that the relationship between burnout and work life balance on turnover intention at Sparks Forest Adventure was 55.3% and 44.7% influenced by other variables. Based on the results of the analysis, it can be concluded that Burnout and Work Life Balance have a significant effect on Turnover Intention in Sparks Forest Adventure Sukabumi. Tujuan dari penelitian ini yaitu untuk mengetahui pengaruh burnout dan work life balance terhadap turnover intention. Metode yang dipakai dalam penelitian ini yaitu metode deskriptif dan asosiatif dengan cara kuantitatif. Teknik pengambilam sampel didalam penelitian ini memakai Teknik sampling jenuh, sampel yang dipilih dalam penelitian ini yaitu sebanyak 63 orang karyawan Sparks Forest Adventure. Teknik analisis data yang dipakai dalam penelitian ini yaitu teknik analisis korelasi ganda, analisis koefisien determinasi, analisis regresi linear berganda, uji signifikan parsial (uji-T) dan uji signifikan simultan (Uji-F). Berdasarkan hasil dari uji koefisien korelasi ganda didapatkan nilai R sebesar 0,743 artinya bahwa ada hubungan yang kuat antara burnout dan work life balance terhadap turnover intention di Sparks Forest Adventure. Hasil uji koefisien determinasi didapatkan dari perolehan nilai (R Square) yaitu sebesar 0,553 artinya hubungan antara burnout dan work life balance terhadap turnover intention di Sparks Forest Adventure terdapat hubungan sebesar 55,3% dan 44,7% dipengaruhi variabel lain. Berdasarkan hasil analisis maka dapat disimpulkan bahwa Burnout dan Work Life Balance berpengaruh signifikan terhadap Turnover Intention pada sparks forest adventure sukabumi.